PANDANGAN HUKUM ABDULLAHI AHMED AN-NA‘IM - Amir, Ahmad Nabil; Abdul Rahman , Tasnim (IAIN Ambon, 2025)
The paper discusses method of legal interpretation as set forth by Abdullahi Ahmed An-Naim in his works. His legal views takes a historical and contextualist approach in interpreting the text with critical reinterpretation of traditional understanding of the texts by taking into account the purpose of the Syari‘ (the Law Giver) as well as the underlying principle and ideal of the Shariah. By way of deconstruction the Shariah embodies new legal postulates contextually deducted from the text which corresponds to the current situation and context. The method of study is based on qualitative technique in the form of content analysis. It draws upon Miles & Huberman’s analytical methods and techniques, namely reducing and presenting data and drawing conclusion. The finding shows that Abdullahi Ahmed An-Naim aspired toward comprehensive and broad range of legal reform by accommodating and fitting the text with the legal provisions and requirement of modern context based on the instrumentality of maslahah. It sought to reform the legal aspects of Islamic law (syariah) through independent reasoning (ijtihad) and collective argument considering the possible spirit and perspective of its viability and continuity which developed and evolved in dynamic historical and cultural context. Keywords: Abdullahi Ahmed An-Naim, deconstruction, Islamic law